Conceptual framework of Performance-Risk Indicators (PRI) associated to building users in higher institution / Natasha Khalil … [et al.] - Khalil, Natasha; Kamaruzzaman, Syahrul Nizam; Nawawi, Abdul Hadi; Husin, Husrul Nizam (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
Rapid expansion of the higher education sectors in particular institutions has become major poles of economic and social growth. To support the adequacy of educational activities, it is important to sustain the performance and services of the building. However, the expanding provision on facilities and range of operations has emerged performance issues in various mandates. Initially the growing students’ population with various learning activities has constituted risk emergence, inefficient of energy use and climate discomfort. It thus potentially decreases the total performance of the building year by year. To sustain the building efficiency, Building Performance Evaluation (BPE) able to play avital role to improve performance issues in higher education building. The notion of assessing building performance is to understand whether the building meets its function and technical objectives. There are many recent studies that divert the principles of building performance into sustainable buildings by emphasizing the vulnerability of risk in building performance. The awareness on prioritizing the comfort and safety of occupants are much concern on the risk aspects perceived towards them. Since the concept of building performance acquires feedback from building users, hence, the selected risk frames in this research context was relatively allied on the impact towards building users, as social factors.